DAIRY PRODUCTION DIAGNOSIS FROM THE PERSPECTIVE OF BUSINESS ECOSYSTEM: STATE OF THE ART IN 2016 - Bonamigo, Andrei; Ferenhof, Helio Aisenberg; Forcellini, Fernando Antonio (Brazilian Journal of Operations & Production Management, 2017)
In the pursuit of identify ways for a better understanding the barriers of the dairy production system, we sought to diagnose them from the perspective of the business ecosystem concept, through a systematic literature review. Thus, we use content analysis to serve as the basis for analysis and discussion of the barriers of dairy production. Resulting a total of fifteen barriers, properly presented and discussed. In addition, we provide some insights to mitigate these barriers. The study presents contribution to the development of dairy production by providing assistance to develop strategies for producers’ cooperatives, government agencies, milk producers, hulling industries products from milk. Based on the perspective of the business ecosystem is possible to have a broader view of the scenario where dairy production occurs and recognize the barriers of dairy production system. And once identified these barriers, it is possible to devise strategies to eliminate or mitigate these barriers.